2005
DOI: 10.1175/jas3477.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Impacts on the Growth of Drops within Simulated Marine Stratocumulus. Part I: Maximum Solar Heating

Abstract: The effects of solar heating at a variety of solar zenith angles (⌰ o ) on the vapor depositional growth of cloud drops, and hence the potential for collection enhancement, is investigated. A large eddy simulation (LES) model is used to predict the evolution of marine stratocumulus clouds subject to changes in ⌰ o . During the course of each simulation, LES output is stored for 600 parcel trajectories and is used to drive an offline microphysical model that includes the influence of radiation on drop growth.Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…We initialize the model with random thermal perturbations to an input sounding that produces thick, overcast stratiform clouds (Hartman and Harrington 2005). A low LWP stratiform cloud was created from that sounding by lowering the vapor mixing ratio by 2.75 g kg 21 above the boundary layer inversion.…”
Section: Dynamic Atmospheric Modelmentioning
confidence: 99%
“…We initialize the model with random thermal perturbations to an input sounding that produces thick, overcast stratiform clouds (Hartman and Harrington 2005). A low LWP stratiform cloud was created from that sounding by lowering the vapor mixing ratio by 2.75 g kg 21 above the boundary layer inversion.…”
Section: Dynamic Atmospheric Modelmentioning
confidence: 99%
“…9 and 10 demonstrate the effect of LW radiant emission in enhancing cloud droplet growth, the opposite effect of SW (solar) radiant absorption could be shown by including it [24][25][26] in the radiation term Q r D, with the possibility that SW radiation could change the sign from negative to positive. This would require estimating absorption of SW radiation, which is more complicated just by the stronger spectral variation of water's absorption coefficient in the SW range compared to the LW range and the smaller absorption efficiency for SW radiation compared with the near unity emission efficiency for LW radiation (different absorption and emission efficiencies would need to be evaluated, as noted previously).…”
Section: Sample Cloud Droplet Radiation Calculationmentioning
confidence: 99%
“…Long-resident droplets also grow on average considerably larger than convective droplets due to condensation induced by longwave radiative cooling, which can speed up rain formation (Roach, 1976;Hartman and Harrington, 2005). In this paper, we isolate the effect of radiation, and investigate how condensation due to radiative cooling alone broadens the cloud-top DSD.…”
Section: Discussionmentioning
confidence: 99%
“…The parcels vary their position following the flow dynamics, so that the TEM can be considered as a Lagrangian model. Harrington (2000) and Hartman and Harrington (2005) used a TEM driven by a LES to show that stratocumulus drizzle is sped up by radiative cooling at parcels that stay close to the top. Similarly, Magaritz et al (2009) used a TEM driven by two-dimensional synthetic turbulence and found that drizzle is initiated in lucky parcels that stay for a long time close to the cloud top.…”
Section: Introductionmentioning
confidence: 99%